New ideologies of forever (Ciudades, 2018)
The chosen discourse to design the fashion of this spring at the end of the century, is already in posesion of a nuclear password, another hitch pennant for the simple-minded, a new broad ideology to pretend to legitimize the construction of a new order in all instances and also, obviously, a new space: competitivity.
Keywords: ideology; urbanism